Outcomes among patients undergoing transcatheter aortic valve replacement with very low baseline gradients - Rahman, Faisal; Mehta, Hetal H.; Resar, Jon R.; Hasan, Rani K.; Marconi, Wendy; Aziz, Hamza; Czarny, Matthew J. (Frontiers in Cardiovascular Medicine, 2023)
Background: While there is evidence that patients with low-flow low-gradient aortic stenosis (AS) benefit from transcatheter aortic valve replacement (TAVR), data are lacking regarding outcomes of patients with a very low mean gradient (VLG).In this retrospective, single-center study of patients with severe AS who underwent TAVR, three groups were defined using baseline mean aortic valve gradient: VLG (≤25 mmHg), low gradient (LG, 26-39 mmHg), and high gradient (HG, ≥40mmHg). The primary outcome was the composite of Kansas City Cardiomyopathy Questionnaire (KCCQ)-12 <45, decrease in KCCQ-12 ≥10 compared to baseline, or death at 1-year.Results: One-thousand six patients were included; 571 HG, 353 LG, and 82 VLG. The median age was 82.1 years (interquartile range [IQR] 76.3-86.9); VLG patients had more baseline comorbidities compared to the other groups. The primary outcome was highest at 1-year in the VLG group (VLG: 46.7%, LG: 29.9%, HG: 23.1%, p=0.002), with no difference between groups after adjustment for baseline characteristics. At baseline, <30% of VLG patients had an excellent or good (50-100) KCCQ-12, whereas more than 75% and 50% had an excellent or good KCCQ-12 at 30-day and 1-year follow-up, respectively.Although patients with VLG undergoing TAVR have a higher rate of poor outcomes at 1-year compared to patients with LG and HG severe AS, this difference is largely attributable to baseline comorbidities. Patients with severe AS undergoing TAVR have significant improvement in health status outcomes regardless of resting mean gradient.